Autophagy and neurodegeneration: Unraveling the role of C9ORF72 in the regulation of autophagy and its relationship to ALS-FTD pathology - Diab, Rim; Pilotto, Federica; Saxena, Smita (Frontiers in Cellular Neuroscience, 2023)
The proper functioning of the cell clearance machinery is critical for neuronal health within the central nervous system. In normal physiological conditions, the cell clearance machinery is actively involved in the elimination of misfolded and toxic proteins throughout the lifetime of an organism. The highly conserved and regulated pathway of autophagy is one of the important processes involved in preventing and neutralizing pathogenic build up of toxic proteins that could eventually lead to the development of neurodegenerative diseases such as Alzheimer’s disease or Amyotrophic lateral sclerosis (ALS). The most common genetic cause of ALS and frontotemporal dementia (FTD) is a hexanucleotide expansion consisting of GGGGCC (G4C2) repeats in the chromosome 9 open reading frame 72 gene (C9ORF72). These abnormally expanded repeats have been implicated in leading to three main modes of disease pathology: loss of function of the C9ORF72 protein, the generation of RNA foci, and the production of dipeptide repeat proteins (DPRs). In this review, we discuss the normal physiological role of C9ORF72 in the autophagy-lysosome pathway (ALP), and present recent research deciphering how dysfunction of the ALP synergizes with C9ORF72 haploinsufficiency, which together with the gain of toxic mechanisms involving hexanucleotide repeat expansions and DPRs, drive the disease process. This review delves further into the interactions of C9ORF72 with RAB proteins involved in endosomal/lysosomal trafficking, and their role in regulating various steps in autophagy and lysosomal pathways. Lastly, the review aims to provides a framework for further investigations of neuronal autophagy in C9ORF72-linked ALS-FTD as well as other neurodegenerative diseases.